PHYSICAL AND CHEMICAL QUALITIES OF FROZEN BEEF WITHIN DIFFERENT THAWING METHOD - Diana, C; Dihansih, Elis; Kardaya, Dede (Universitas Djuanda Bogor, 2018)
Different thawing metods were applied to frozen beef in order for evaluating both the physical and chemical qualities. The study used a completely randomized design with six treatments as follow:1) fresh beef as control, 2) frozen beef allowed at room temperature (27-300C) until internaltemperature of beef reached 00C (became unfrozen), 3) Frozen beef thawed at refrigerator temperature, i.e. 8-100C, 4) Frozen beef thawed at running water which its temperature range within 25-280C, 5) Frozen beef thawed by boiling water (1000C), and 6) Frozen beef thawed by hot water (<1000C). Every treatment was made in three replicates. Results of the study repealed that frozen beef thawed by running water, hot water, or boiling water resulted in better physical qualities than the one thawed by refrigerator temperature (P<0.05). All thawing methods did not significantly affect on chemical qualities of the beef (P>0.05). Moreover, all frozen beef showed similar chemical qualities to the fresh beef.